The Soil Respiration of Coal Mine Heaps’ Novel Ecosystems in Relation to Biomass and Biotic Parameters - Radosz, Łukasz; Chmura, Damian; Prostański, Dariusz; Woźniak, Gabriela (Energies (Basel), 2023)
The biodiversity, including the diversity of autotrophic organisms of mostly plant species, assembled in vegetation patches and its impact on the course of ecosystem processes is still a key subject of research in natural sciences around the world. Certain aspects of the relationship between biodiversity and CO2 release processes have been studied only in some natural and semi-natural ecosystems (semi-natural ecosystems such as meadow or grasslands). In contrast, very little is known about the biotic parameters related to natural processes and the functioning of novel ecosystems. This study was performed on post-black coal mining heaps. The studied sites were established on carboniferous mineral material. Among the considered biotic parameters, the vegetation plant species composition, soil organic matter, soil enzymatic activity, soil fauna presence, and the plant species biomass were studied. The aim of the research was to analyse the influence of the selected biotic factors on the CO2 release from the mineral material of black coal mining heaps’ novel ecosystems. The range of CO2 release at the analysed sites was 0.00158–1.21462 [g CO2/m2/h]. The activity of soil enzymes such as dehydrogenase, acid phosphatase, and basic phosphatase was positively correlated with the amount of CO2 released, however, there was no correlation between urease activity and CO2 emissions from the soil. In our study, a comparison of the soil organic matter developed under the vegetation types studied and CO2 release (rate) showed a dependence on vegetation type. The amount of biomass was not linearly correlated with CO2 release from the soil. The presence of soil fauna displayed a positive effect on CO2 release.